2013
DOI: 10.1371/journal.pone.0069508
|View full text |Cite
|
Sign up to set email alerts
|

Local Inflammation Exacerbates the Severity of Staphylococcus aureus Skin Infection

Abstract: Staphylococcus aureus is the leading cause of skin infections. In a mouse model of S. aureus skin infection, we found that lesion size did not correlate with bacterial burden. Athymic nude mice had smaller skin lesions that contained lower levels of myeloperoxidase, IL-17A, and CXCL1, compared with wild type mice, although there was no difference in bacterial burden. T cell deficiency did not explain the difference in lesion size, because TCR βδ (-/-) mice did not have smaller lesions, and adoptive transfer of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…There was no apparent effect on bacterial CFU at 24 h postinfection in any of the treatment groups relative to the R347 isotype control. Similar to other reports, lesion size in this model is not dependent on bacterial burden (Table 2) but is primarily AT mediated (9,(21)(22)(23)(24). However, treatment with vancomycin or MEDI4893*-vancomycin accelerated bacterial burden reduction, resulting in significant CFU reductions at 3 (P Ͻ 0.05) and 7 (P Ͻ 0.05) days postinfection relative to R347.…”
Section: Resultssupporting
confidence: 87%
“…There was no apparent effect on bacterial CFU at 24 h postinfection in any of the treatment groups relative to the R347 isotype control. Similar to other reports, lesion size in this model is not dependent on bacterial burden (Table 2) but is primarily AT mediated (9,(21)(22)(23)(24). However, treatment with vancomycin or MEDI4893*-vancomycin accelerated bacterial burden reduction, resulting in significant CFU reductions at 3 (P Ͻ 0.05) and 7 (P Ͻ 0.05) days postinfection relative to R347.…”
Section: Resultssupporting
confidence: 87%
“…Multiple studies in addition to our findings have now illustrated a lack of direct, temporal correlation between S. aureus recovery from the infected tissue and measurements of disease severity [8,9,22,45,50], suggesting that the clinical manifestations of disease represent the aggregate balance of bacterial insults to resident and recruited cells and the host inflammatory response [51]. This response can be well-directed to facilitate pathogen clearance in the given tissue, or overly aggressive, leading to exacerbated injury.…”
Section: Discussionmentioning
confidence: 69%
“…Together, these data suggest that toxin-induced immunostimulation establishes a pro-inflammatory skin environment that benefits the host, limiting the consequences of S. aureus infection. In contrast to these findings, a recent study examining athymic nude mice noted decreased staphylococcal skin lesion size in these mice [45]. The authors concluded that local inflammation promotes increased severity of S. aureus skin infection, a finding that will require further mechanistic investigation in light of the more substantial alterations of immunologic function in nude mice.…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, bacterial biofilms appear to play an important role in increasing the difficulty of treating these ulcers (40). Furthermore, it has been proven recently that the clinical severity of S. aureus skin infection is driven by the inflammatory response to the bacteria rather than the bacterial burden (42)(43)(44). Taken together, the characteristics of the presented peptides with combined bactericidal, antibiofilm, and anti-inflammatory effect may offer an effective way for treating staphylococcal skin infection.…”
Section: Discussionmentioning
confidence: 99%